2021
DOI: 10.3390/jcm10184048
|View full text |Cite
|
Sign up to set email alerts
|

Single Surgeon Experience with 500 Cases of the Robotic Bilateral Axillary Breast Approach (BABA) for Thyroid Surgery Using the Da-Vinci Xi System

Abstract: Objectives: Robotic bilateral axillary breast approach (BABA) thyroid surgery began in 2008 and is now one of the most widely used remote-access thyroid surgeries worldwide. This study aimed to analyze the results of 500 robotic BABA thyroid surgeries performed in a single institution in Korea compared with open thyroid surgery. Methods: From December 2018 to March 2020, 502 robotic BABA thyroidectomies (RTs) and 531 conventional open thyroidectomies (OTs) were performed in our institution by a single endocrin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Since introduction of robotic BABA thyroidectomy in 2008, robotic BABA thyroidectomy has become one of the most remarkable remote-access approaches globally, particularly in Korea 11 . Over time, many surgeons have demonstrated the safety of robotic BABA thyroidectomy and have tried to overcome existing surgical criteria 8,[14][15][16] . A recent study also suggested that surgical indications might extend up to 4 cm for malignant tumors and up to 8 cm for benign nodules 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Since introduction of robotic BABA thyroidectomy in 2008, robotic BABA thyroidectomy has become one of the most remarkable remote-access approaches globally, particularly in Korea 11 . Over time, many surgeons have demonstrated the safety of robotic BABA thyroidectomy and have tried to overcome existing surgical criteria 8,[14][15][16] . A recent study also suggested that surgical indications might extend up to 4 cm for malignant tumors and up to 8 cm for benign nodules 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The approach of the procedure is chosen based on the patient anatomy, the extent of the disease, and cosmetic preferences. In recent times, the robotic thyroidectomy technique that has been predominantly favored and implemented is the bilateral axillo-breast approach [70]. A study including 500 patients undergoing the robotic BABA revealed that the rate of transient vocal cord palsy and hypoparathyroidism is significantly lower compared to open thyroidectomy [70].…”
Section: Robotic Thyroidectomymentioning
confidence: 99%
“…In recent times, the robotic thyroidectomy technique that has been predominantly favored and implemented is the bilateral axillo-breast approach [70]. A study including 500 patients undergoing the robotic BABA revealed that the rate of transient vocal cord palsy and hypoparathyroidism is significantly lower compared to open thyroidectomy [70]. Moreover, the BABA has emerged as a more conducive technique for total thyroidectomies and the excision of large goiters compared to the transaxillary approach, which is attributed to its enhanced anatomical accessibility and the precision facilitating the comprehensive removal of the thyroid gland [71,72].…”
Section: Robotic Thyroidectomymentioning
confidence: 99%